Significance of Sacral Index in Estimation of Sex in Sacra of Cadavers in Bangladesh (Bangladesh Journal of Anatomy, 2014)
Context : The bones of the body are the last to pass away after death, next to enamel of teeth. Hence, in establishing the personal identity with respect to sex, age and stature, medico legal experts, anatomists and anthropologists use the skeletal materials for giving their opinion. Sex-dependent differences have been noted in the pelvic bone anatomy, and so differences exist in male and female sacrum. The aim of this study was to collect data regarding morphometric measurements of maximum length and breadth of sacrum and to find out possible variations of sacral index in different individuals in relation to sex. Material and Methods: A Cross-sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, on 172 (one hundred seventy two) adult human dry sacra of unknown sex. The study samples were distributed in male and female sex groups by discriminant function analysis. All the samples were studied morphologically. Sacral length and breadth were measured with the help of digital slide calipers. Result : The mean sacral index in male and female were 97.88±6.16 % and 112.69±10.17 % respectively. Female has the greater sacral index than male (P